The Analysis and Simulation of Consumer Behavior Towards Product Boycotts Using Mathematical Modeling in North Sangatta District - Jusman, Jusman; Side, Syafruddin; Syam, Rahmat; Yusuf SAP, Andi Muh. Ridho (Jurusan Matematika FMIPA UNM, 2025)
This study aims to analyze and simulate a mathematical model of product boycott behavior in North Sangatta District using a modified SEIRS model approach. This model divides the population into four compartments: Susceptible (S), Exposed (E), Infected (I), and Recovered (R). Primary data were obtained through a survey of individuals aged 15-60 years living in North Sangatta District. The SEIRS-type mathematical model was used to determine the equilibrium point. The analysis showed that the basic reproduction number , indicating that an individual who boys can influence others to do the same. Stability analysis shows that when , the boycott-free equilibrium point is unstable, while the endemic equilibrium point is locally asymptotically stable. This means that individuals who boycott will remain in the population. Simulations show that reducing the transition rate from susceptible to exposed and from exposed to boycotts, as well as increasing the recovery rate, can be a solution to reduce the impact of boycotts.